2020
DOI: 10.1177/0020720920940594
|View full text |Cite
|
Sign up to set email alerts
|

Moral education teaching in colleges and universities based on the application of multimedia technology

Abstract: In the recent past, Due to continuous development in the field of multimedia technology on moral education teaching in colleges and universities, Students interest and enrollment in smart classrooms with multimedia technology are enhancing worldwide due to diverse demands on high end technologies on moral studies for interactive teaching learning process. At present scenario due to inefficient usage of technology for higher education in colleges and universities, teachers and mentors need to educate themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For real and objective reflects the 020 education mode in the teaching status quo of contemporary college students political education courses and teaching effect, the author randomly the in-service teacher, counselor, and colleges and universities thought politics theory class teacher has carried on the QQ online interview [10], in the case of all respondents actively cooperate with, this a total of 650 copies of questionnaires, including back 624 questionnaires, of which 593 valid, 31 is invalid. This research experiment steps as shown in figure 2, the first design the teaching process, before the start of the course to understand students' ability of learning assembly language, in order to test group divided into two parts, that in comparative classes and experimental classes, procedural 020 teaching pattern for experimental class students evaluation model, and according to the experimental situation learners can be divided into three categories: learners of learners of class A and class B and class C learner [9], and integrated the three kinds of dynamic data in the learning process, learners through 020 teaching process evaluation, complete data collection; At the same time, the control group of learners to make the traditional summative evaluation, complete the corresponding data collection; The data of the two groups were analyzed to objectively evaluate learners' learning enthusiasm and performance, and finally the corresponding conclusions were drawn [11].…”
Section: Research Objectsmentioning
confidence: 99%
“…For real and objective reflects the 020 education mode in the teaching status quo of contemporary college students political education courses and teaching effect, the author randomly the in-service teacher, counselor, and colleges and universities thought politics theory class teacher has carried on the QQ online interview [10], in the case of all respondents actively cooperate with, this a total of 650 copies of questionnaires, including back 624 questionnaires, of which 593 valid, 31 is invalid. This research experiment steps as shown in figure 2, the first design the teaching process, before the start of the course to understand students' ability of learning assembly language, in order to test group divided into two parts, that in comparative classes and experimental classes, procedural 020 teaching pattern for experimental class students evaluation model, and according to the experimental situation learners can be divided into three categories: learners of learners of class A and class B and class C learner [9], and integrated the three kinds of dynamic data in the learning process, learners through 020 teaching process evaluation, complete data collection; At the same time, the control group of learners to make the traditional summative evaluation, complete the corresponding data collection; The data of the two groups were analyzed to objectively evaluate learners' learning enthusiasm and performance, and finally the corresponding conclusions were drawn [11].…”
Section: Research Objectsmentioning
confidence: 99%
“…(2020) explored university teachers' willingness to adopt the smart classroom from the perspectives of technological factors and external pressure and found that relative advantages, normative pressure and other factors could positively affect teachers' adoption willingness. Teng et al. (2020) researched the usage intention of university teachers in smart classrooms to further promote moral education in universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, there are few studies on the behaviors of users of smart classrooms (Lu et al, 2022). Previous studies have mostly focused on teachers' willingness to adopt or use smart classrooms (Selim et al, 2020;Teng et al, 2020), but there is a lack of deeper research on teachers' switching intention from traditional to smart classrooms. The emergence of the smart classroom as a kind of new technology is essentially a change in classroom teaching methods (Kwet and Prinsloo, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meaningful scenario, multimedia motivates and piques curiosity in learning. Students' interest in smart classrooms with multimedia technology is growing around the world resulting in demands for high-end technologies for interactive teaching and learning (TENG ET AL., 2020). Therefore, educators must continuously train themselves and enhance their…”
Section: Introductionmentioning
confidence: 99%